(untitled) (Journal of Engineering, 2014)
Creep testing is an important part of the characterization of composite materials. It is crucial to determine long-term deflection levels and time-to-failure for these advanced materials. The work is carried out to investigate creep behavior on isotropic composite columns. Isotropy property was obtained by making a new type of composite made from a paste of particles of carbon fibers mixed with epoxy resin and E-glass particles mixed with epoxy resin. This type of manufacturing process can be called the compression mold composite or the squeeze mold composite. Experimental work was carried out with changing the fiber concentration (30, 40 and 50% mass fraction), cross section shape, and type of composite. The creep results showed that the higher the fiber concentration, the more the creep resistance. Type of fiber plays a very critical role, where carbon/epoxy composite showed much higher creep resistance and also showed much higher modulus of elasticity than the E-glass/epoxy composite. Specimen shape factor noticed to play a very small role. However, square cross sectional area showed slightly higher resistance for creep than the rectangular cross sectional area. This difference is not critical and can be ignored. F.E.M simulation with ANSYS Inc. software was implied and results were compatible with the experimental work with a maximum discrepancy of (17.24%).